Sensitivity and Specificity of Color Duplex Ultrasound Measurement in the Estimation of Internal Carotid Artery Stenosis - Asadullah, Kavita Satiwan, Sumera Mahar, Muhammad Faham, Marya Hameed, Hamid Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stroke is that the world’s leading reason for death and major incapacity. Arterial sclerosis is answerable for over half-hour of all ischemic strokes. Plaque morphology has recently been discovered to assist within the prediction of arterial sclerosis clinical behavior and stroke risk. Purpose: The goal of this study was to gauge the frequency and diagnostic exactitude of artery Doppler imaging to detect arterial blood vessel pathology. Methods: This cross-sectional study was conducted in Combined Military Hospital, Peshawar from1st August 2019 to 31st March 2020. A total of 120 patients were randomly selected. The inclusion criteria was having ischemic cerebrovascular stroke. Doppler ultrasound was performed in every patient by a consultant radiologist. Doppler ultrasound findings were compared with Carotid artery stenosis reports. Results: Mean age in this study was 63.07±3.76 years. Mean duration of disease was 1 year ±3.32 months. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of Doppler Ultrasound were 89.5, 76.20, 45.5, 93.88 and 76.9% respectively. The areas under the ROC curves ranged between 0.89 and 0.90 for the laboratory A device and between 0.90 and 0.92 for the laboratory B device. In laboratories A and B, the areas under the ROC curves for ICA PSV were 0.90 and 0.92, respectively. Similar effects were observed when occlusion-affected patients were omitted (0.89 to 0.91, laboratory A; 0.90 to 0.93, laboratory B). Despite the fact that the diagnostic accuracy of the two devices was equivalent, two points on the ROC curves corresponding to the same cut point were infrequently near. Practical implication: The study compared the techniques of Doppler ultrasound for the diagnosis of carotid artery stenosis in patients and measured the best predicted percent angiographic stenosis differed between two vascular laboratories and paved the way for clinicians to focus of the diagnosis of carotid artery stenosis by DU. Conclusion: With the advancement in technology, the accuracy of carotid artery stenosis diagnosis has significantly improved over the decades. From measuring the narrowing carotid artery diameter to evaluating the increased velocity field near the obstruction/lesion site, the identification of additional parameters to characterize plaque vulnerability has become more important in the carotid artery. Keywords: Angiography; Carotid artery stenosis; Cerebrovascular ischemia; Doppler ultrasound sensitivity.